2019
DOI: 10.1063/1.5100028
|View full text |Cite
|
Sign up to set email alerts
|

Review of the relativistic magnetron

Abstract: The cavity magnetron is the most compact, efficient source of high-power microwave (HPM) radiation. The imprint that the magnetron has had on the world is comparable to the invention of the nuclear bomb. High- and low-power magnetrons are used in many applications, such as radar systems, plasma generation for semiconductor processing, and—the most common—microwave ovens for personal and industrial use. Since the invention of the magnetron in 1921 by Hull, scientists and engineers have improved and optimized ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…As high power microwave (HPM) sources have gradually matured for at least four decades [1]- [7], HPM technology entered widespread civilian and military use. An annular explosive emission cathode (EEC) is widely utilized in the HPM devices to generate an intense relativistic electron beam (IREB).…”
Section: Introductionmentioning
confidence: 99%
“…As high power microwave (HPM) sources have gradually matured for at least four decades [1]- [7], HPM technology entered widespread civilian and military use. An annular explosive emission cathode (EEC) is widely utilized in the HPM devices to generate an intense relativistic electron beam (IREB).…”
Section: Introductionmentioning
confidence: 99%
“…printed SWSs fully in metal [5]. Due to the dimensions of the device that was ultimately selected, 3D printing in metal was not possible because of the wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Among all, the relativistic magnetron (RM) is one of the most attractive high‐power microwave (HPM) sources, due to its compactness and high efficiency. Since the first RM is experimentally developed by Bekefi and Orzechowski at MIT in 1976 [9], lots of efforts have been made to improve the efficiency and the compactness [4]. A good review of magnetrons can be found in recent literature [4].…”
Section: Introductionmentioning
confidence: 99%
“…The term 'relativistic' refers to velocities closer to the speed of light where the electron beams with high voltage of hundreds of kV and high current of tens kA are used. The progress results from three main developments: conventional microwave devices such as klystrons [1], backward-wave oscillators [2,3] and magnetrons [4] with the use of higher currents and voltages; high current devices such as vircators [5] and magnetically insulated local oscillators without external magnetic field [6]; and fast-wave devices such as gyrotrons [7] and free-electron lasers [8] which can generate higher powers at higher frequencies than conventional devices making use of relativistic effects. Among all, the relativistic magnetron (RM) is one of the most attractive high-power microwave (HPM) sources, due to its compactness and high efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation